PENGARUH DIGITAL MARKETING DAN ELECTRONIC WORD OF MOUTH TERHADAP TINGKAT PENJUALAN HB COLLECTION DI SHOPEE - Santi, Neng; Komalasari, Yunika; Yuliyana, Wulan (Universitas Logistik dan Bisnis Internasional, 2025)
Digital marketing is a marketing strategy carried out online to increase the visibility and attractiveness of products, while electronic word of mouth is informal communication between consumers via digital media that can influence purchasing decisions. This research aims to find out the picture of digital marketing, electronic word of mouth and sales levels. Then, to test the partial influence of digital marketing on sales levels, electronic word of mouth on sales levels, and simultaneously the influence of digital marketing and electronic word of mouth on HB Collection sales levels on Shopee. The data analysis technique uses descriptive verification with a non-probability sampling method of 100 respondents. The research results show that digital marketing and electronic word of mouth have a significantly positive effect on the level of HB Collection sales on Shopee.